Viscoelasticity of frozen/thawed egg yolk as affected by salts, sucrose and glycerol - Telis, VRN; Kieckbusch, T. G. (Inst Food Technologists, 1998)
Based on dynamic rheological measurements, sucrose, glycerol and magnesium chloride (MgCl2) prevented egg yolk gelation at concentrations of 2% and higher, These additives showed improved cryoprotectant effects as their concentrations were increased, Sodium chloride (NaCl) at higher than 2% also prevented gelation but at 10%, it caused a considerable increase in viscosity of unfrozen yolk, Calcium chloride (CaCl2) showed an opposite effect, promoting protein coagulation before freezing, Samples with 2% CaCl2 gelled completely after 36h at -24 degrees C, Before freezing, potassium chloride (KCl) in the range 2-10% had an effect similar to that of NaCl, However, after freezing its effect changed, Yolk with 2% KCl, frozen 36h at -24 degrees C, showed very elastic behavior.
Keywords: egg yolk; freezing; gelation; additives; viscoelasticity